2011
DOI: 10.5897/ajb10.148
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficiency of a yeast biofilter in the treatment of abattoir wastewater

Abstract: A yeast biofilter consisting of Candida krusei, Candida morbosa, Torulopsis dattila, Torulopsis glabrata, and Saccharomyces chevalieri was constructed to bioremediate abattoir wastewater. Potato peels were used as filter bed for the growth of the yeasts. Wastewater samples were collected from three different points in Sokoto (Nigeria) abattoir and the physiochemical as well as the microbiological qualities of the wastewater were determined before and after biofiltration. The results revealed that after the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Yeasts are of the microorganism that is efficient in biodegradation of organic pollutants in sewage water. Abdullahi [30] in their study showed the efficiency of Candida and Rhodotorula in reducing concentrations of pollutants and the use of these yeast in biofiltration with efficiently for more than 40%, as well as, Woertz et al [31] demonstrated the effectiveness of black yeast Exophialalecanii-corni to eliminate of toluene from waste gas streams. The results of current study [32] proved that the positive influences magnetic are affected by positive and negative ions and the amount of organic material.…”
Section: The Magnetic Field Effect On the Reduction Of Concentrationsmentioning
confidence: 97%
“…Yeasts are of the microorganism that is efficient in biodegradation of organic pollutants in sewage water. Abdullahi [30] in their study showed the efficiency of Candida and Rhodotorula in reducing concentrations of pollutants and the use of these yeast in biofiltration with efficiently for more than 40%, as well as, Woertz et al [31] demonstrated the effectiveness of black yeast Exophialalecanii-corni to eliminate of toluene from waste gas streams. The results of current study [32] proved that the positive influences magnetic are affected by positive and negative ions and the amount of organic material.…”
Section: The Magnetic Field Effect On the Reduction Of Concentrationsmentioning
confidence: 97%
“…Table (8) shows the percentage of reducing the concentration of pollutants from wastewater in terms of the factors COD, TOC, TP, and TN for the control treatment by using the multiple biofilters at a treatment period of 18 hrs., as the concentrations of the factors before treatment were 560, 172, 25 and 42 ppm, respectively. As well as, after 18 hours of treatment, distributed in three stages (6 hrs.…”
Section: Efficiency Of the Multiple Biofilters In Reducing Pollutants...mentioning
confidence: 99%
“…Yeasts are of the microorganism that are efficient in biodegradation of organic pollutants in sewage water. Abdullahi et al (2011) in their study showed the efficiency of Candida and Rhodotorula in reducing concentrations of pollutants and the use of these yeast in biofiltration with efficiently for more than 40% ,as well as, Woertz et al( 2001) demonstrated the effectiveness of black yeast Exophiala lecanii-corni to eliminate of toluene from waste gas streams .The results of current study agreed with Coey and Cass( 2000) proved that the positive influences magnetic is affected by positive and negative ions and the amount of organic material . The effect is physically through the arrangement of molecules in the watery body and reduces the surface tension , so increase the solubility of oxygen, which leads to increase oxidative aerobic for organic and inorganic pollutants.…”
Section: -The Magnetic Field Effect On the Reduction Of Concentratiomentioning
confidence: 99%